Debt-Constrained Asset Markets - Kehoe, T. J.; Levine, D. K. (Review of Economic Studies, 1993)
We develop a theory of general equilibrium with endogenous debt limits in the form of individual rationality constraints similar to those in the dynamic consistency literature. If an agent defaults on a contract, he can be excluded from future contingent claims markets trading and can have his assets seized. He cannot be excluded from spot markets trading, however, and he has some private endowments that cannot be seized. All information is publicly held and common knowledge, and there is a complete set of contingent claims markets. Since there is complete information, an agent cannot enter into a contract in which he would have an incentive to default in some state. In general there is only partial insurance: variations in consumption may be imperfectly correlated across agents; interest rates may be lower than they would be without constraints; and equilibria may be Pareto ranked.